If you build it, who will come? Exploring the effects of rapid transit on residential movements in Metro Vancouver - Kapatsila, Bogdan; Rea, Jordan D.; Grisé, Emily (Journal of Transport and Land Use, 2024)
As cities across the world embrace the benefits of rapid transit technology and invest in the expansion of existing infrastructure or plan for the introduction of new lines, the differences in both benefits and externalities that bus rapid transit (BRT) and rail rapid transit (RRT) bring remain unclear. This study aimed to address that gap and understand whether there was a distinction in impacts on the residential migration of households in different income and residential tenure groups as the result of BRT and RRT projects. This was achieved by exploring the effects of both modes in the same metropolitan region—metro Vancouver. This study used three BRT and three RRT lines that were in service for all or part of the 20 years spanning 1996 through 2016 to assess the rates of in-movement of households by income in Census Tracts (CTs) within 800 meters (½-mile) of a given rapid line. Our analysis suggested that areas adjacent to the Expo-Millennium RRT Corridor saw fewer in-movers between the 2001 Census and the 2016 Census than the areas without rapid transit infrastructure, while the same was true for the CTs affected by BRT lines and that had a larger than average share of new housing while holding everything else (e.g., housing supply) constant. While we did not find evidence to state that the presence of rapid transit infrastructure disproportionately affected any one of the income groups, our analysis suggested that there were more affluent renters moving in along the RRT and BRT lines. At the same time, the share of low-income renters that moved into areas close to rapid transit lines remained relatively stable. This research added a unique perspective to the debate cities and transport agencies have been experiencing with respect to decisions around the investment into different transport technologies and contributed to the argument for the need to carefully plan and provide rapid transit infrastructure together with affordable and diverse housing options.